2018
DOI: 10.1038/s41598-018-28780-5
|View full text |Cite
|
Sign up to set email alerts
|

Multi-spectral optical imaging of the spatiotemporal dynamics of ionospheric intermittent turbulence

Abstract: Equatorial plasma depletions have significant impact on radio wave propagation in the upper atmosphere, causing rapid fluctuations in the power of radio signals used in telecommunication and GPS navigation, thus playing a crucial role in space weather impacts. Complex structuring and self-organization of equatorial plasma depletions involving bifurcation, connection, disconnection and reconnection are the signatures of nonlinear evolution of interchange instability and secondary instabilities, responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Chian et al (2018) extended the observational study of Sahai et al (2006) and reported airglow images of neighboring plasma bubbles disconnecting and reconnecting. In the airglow images reported by Chian et al (2018), they observed that the first disconnection occurs on the east side and after some time, the detached part is captured by an adjacent plasma bubble on the west side in the image.…”
Section: Databasementioning
confidence: 76%
See 1 more Smart Citation
“…Chian et al (2018) extended the observational study of Sahai et al (2006) and reported airglow images of neighboring plasma bubbles disconnecting and reconnecting. In the airglow images reported by Chian et al (2018), they observed that the first disconnection occurs on the east side and after some time, the detached part is captured by an adjacent plasma bubble on the west side in the image.…”
Section: Databasementioning
confidence: 76%
“…It is worth mentioning that the airglow images reported by Chian et al. (2018) were obtained on 28 September 2002 in another location in Brazil.…”
Section: Observations: Disconnection and Reconnectionmentioning
confidence: 89%
“…Refs. [12,17] also reported disconnection and reconnection of plasma bubbles. The reconnection features of the plasma bubbles observed are similar to the plasma bubbles' ionospheric electrostatic reconnection reported by [15].…”
Section: Introductionmentioning
confidence: 94%
“…Many researchers have studied the dynamics of EPBs in the context of their zonal drifts, occurrence statistics, morphological evolution etc (e.g., Chian et al., 2018; Gurav et al., 2019; Kakad et al., 2017; Sharma et al., 2017 etc.). The EPBs frequently occur in high solar activity but during low solar activity period a stronger perturbation is needed for their development (e.g., Buhari et al., 2017) which could either be of wave‐like seed of lower atmospheric origin (e.g., Taori et al., 2011) or of electrical origin such as magnetic disturbance (e.g., Sripathi et al., 2018).…”
Section: Introductionmentioning
confidence: 99%